How to attract Millennials & Generation Z into an organization in the business area in Portugal - Barreto, Ana Rita Alves (2018)
Young generations (Millennials and Generation Z) are the new workforce and in view of this, work conditions should adapt to them. To attract young generations, organizations need to know these generations well and what organizational characteristics they prefer. Therefore, this study aimed to understand which organizational characteristics influence organizational attractiveness for Millennials and Generation Z the most, in particular within the Portuguese business context. Firstly, the results of this study indicated that the 16 organizational characteristics, found relevant based on the literature review, can be included in 7 more global dimensions. And secondly, the results of this research showed that to attract young people – both Millennials and Generation Z – to an organization in the business area in Portugal, the most important dimension to consider is dimension 1. Conditions, which encompasses the workplace conditions and security, a good environment, organizational flexibility (related to task variety), recognition (related to conditions to gain rewards) and communication and feedback/self-expression.